Oil mill analysis in Syria [printed version also available in Arabic] - Issa N.; Bourghoul A.; Zakaria M.; Nus B.E.; Jaffar A.M.; Contento F.; Montel G.L. (Syrian national strategic plan for olive oil quality : final report, 2007)
This paper shows the results of the recognition and analysis of the olive oil production activity in the different areas in Syria in 2004 and 2005. Analyses have been conducted on 417 mills, half of those (both with centrifugal and pressure system) now working in the 8 main olive oil regions in the country (Daraa, Aleppo, Idleb, Lattakia, Tartous, Homs, Damascus, Hama). The data (2004 and 2005 olive oil seasons) is related to oil production, olive storing management, mill work capacity, technological degree of the plant and its management, process parameters set-up, oil storage systems. Activity has underlined the points of strength and weakness of the sector, allowing to individualize the possible interventions (micro and macro) and some suggestions related to the improvement of the organization and management of the plant from an oil quality improvement point of view.